Convexity of the Solution Set of a Pseudoconvex Inequality in Riemannian Manifolds. (4th April 2018) - Barani, A.
ABSTRACT: Some equivalent conditions for convexity of the solution set of a pseudoconvex inequality are presented. These conditions turn out to be very useful in characterizing the solution sets of optimization problems of pseudoconvex functions defined on Riemannian manifold.